Pendeteksi Kadar Asap Di Dalam Galley MT. Supreme Star Menggunakan Nodemcu ESP32 - Sony Akbar S; Agus Dwi Santoso; Anak Agung Istri S.W (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
This research aims to design and develop a smoke level detection device based on NodeMCU ESP32 with a room-scale ratio of 1:10. The issue at hand is the occurrence of two false alarms during sailing practices on the MT. SUPREME STAR due to the oversight of the galley Exhaust Fan activation by the cook, resulting in kitchen smoke escaping the room. The designed device is equipped with 4 MQ-135 sensors and an LCD, along with 4 ACS712 sensors to measure the smoke density in the galley in terms of ppm (Part Per Million). LED serves as a parameter for CO (Carbon Monoxide), and ACS712 is utilized to detect mA, determining whether the sensor can activate the Exhaust Fan, indicated by the detected mA. This research includes designing a device to detect smoke levels and automatically activate the Exhaust Fan, as well as understanding the operation of smoke sensors and the NodeMCU ESP32 Microcontroller. By using the "trial and error" research method, namely a series of experiments carried out repeatedly using different methods and materials. Test results indicate that the MQ-135 sensor has an average error ranging from -7.5% to +5.69%, influenced by input voltage. Additionally, IoT test results show that some sensors face difficulty in transmitting data due to voltage drop when Wi-Fi is enabLED. Overall system testing demonstrates that the device effectively controls smoke in the galley. The Exhaust Fan operates according to the predetermined program, and the LED provides an indicator of smoke opacity in accordance with the Air Pollution Standard Index. The MQ-135 sensor can prevent smoke emissions by automatically activating the Exhaust Fan when smoke levels are detected above 30 ppm. Thus, this device prototype can be a solution to address false alarm incidents, and its success indicates the potential use of MQ-135 sensors in the automation of smoke control systems in enclosed spaces.